The role of A-kinase anchoring proteins in cardiac oxidative stress. (11th October 2019) - Diviani, Dario; Osman, Halima; Delaunay, Marion; Kaiser, Simon
Abstract: Cardiac stress initiates a pathological remodeling process that is associated with cardiomyocyte loss and fibrosis that ultimately leads to heart failure. In the injured heart, a pathologically elevated synthesis of reactive oxygen species (ROS) is the main driver of oxidative stress and consequent cardiomyocyte dysfunction and death. In this context, the cAMP-dependent protein kinase (PKA) plays a central role in regulating signaling pathways that protect the heart against ROS-induced cardiac damage. In cardiac cells, spatiotemporal regulation of PKA activity is controlled by A-kinase anchoring proteins (AKAPs). This family of scaffolding proteins tether PKA and other transduction enzymes at subcellular microdomains where they can co-ordinate cellular responses regulating oxidative stress. In this review, we will discuss recent literature illustrating the role of PKA and AKAPs in modulating the detrimental impact of ROS production on cardiac function.